Legal Protection For Breastfeeding Female Drug Concerts And The Children Of Prisoners (Study At Class Iii Women's Correctional Institution Mataram) - Amiruddin; Rodliyah; Pancaningrum, Rina Khairani (Faculty of Law, University of Mataram, 2024)
Perpetrators of criminal acts may be of any gender, as criminal behavior is not limited by gender. When offering protection and support to women who commit crimes, especially those who are breastfeeding, it is crucial to recognize the inherent differences between men and women. It is essential to consider the legislative policy regarding female drug convicts who breastfeed and the children of prisoners in correctional institutions, along with the practical implementation of this policy at the Mataram Class III Women's Correctional Institution. It is crucial to recognize the impact of a mother's presence and living conditions on a child's growth and development. Given the context, it is prudent for the author to conduct a comprehensive review of the imprisonment policy for women convicted of narcotics offenses, especially those who are breastfeeding, and the children of incarcerated individuals. The research methodology employed in this study is normative-empirical legal research, utilizing three distinct approaches: the statutory approach, the conceptual approach, and the sociological approach. The legislative policy regarding female drug convicts who are breastfeeding and the children of prisoners in Correctional Institutions is outlined in Article 9 and Article 62, Paragraphs (1), (2), and (4) of Law Number 22 of 2022 concerning Corrections. The implementation of policies concerning female drug convict mothers who are breastfeeding and their children at the Mataram Class III Women's Penitentiary refers to Law Number 22 of 2022 on Penitentiaries, Government Regulation Number 32 of 1999 concerning the Requirements and Procedures for Implementing the Rights of Inmates, and Law Number 23 of 2002 concerning Child Protection.